KEPUASAN MAHASISWA UBJJ-UT BANDUNG TERHADAP MANAJEMEN PENGELOLAAN BIMBINGAN AKADEMIK PRAKTIKUM SELAMA PANDEMI TAHUN 2021 - Maman Sudirman; Angga Sucitra Hendrayana; Dina Thaib (Idaarah: Jurnal Manajemen Pendidikan, 2022)
This study aims to analyze the management of academic counseling for students who participated in laboratory work. Five functions of academic counseling management were analyzed: organizing, planning, controlling, communicating, and directing. The method used in this research is descriptive quantitative. The sample in this study was 32 students who participated in the 2021 laboratories working at UPBJJ-UT Bandung. The instrument used is a questionnaire in the form of a Likert scale. From the data processed, all the average values ​​of the 20 statement items are close to the maximum value (5). It can conclude that the laboratory work management at UPBJJ-UT Bandung is adequate and going as expected. The students' opinions regarding completeness can still be considered feasible during laboratory work activities.